2009
DOI: 10.1080/02691720903374034
|View full text |Cite
|
Sign up to set email alerts
|

Reading Hurricane Katrina: Information Sources and Decision‐making in Response to a Natural Disaster

Abstract: In this paper we analyze results from 114 face-to-face qualitative interviews of people who had evacuated from the New Orleans area in the wake of Hurricane Katrina, interviews that were completed within weeks of the 2005 storm in most cases. Our goal was to understand the role information and knowledge played in people's decisions to leave the area. Contrary to the conventional wisdom underlying many disaster communication studies, we found that our interviewees almost always had extensive storm-related infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…They typically turn first to their local television station for information and then seek confirmation from other sources such as national television stations, cable weather stations, websites, and social networks (Dash and Gladwin 2007;Zhang et al 2007;Lazo et al 2009;Taylor et al 2009;Morss and Hayden 2010;Sherman-Morris et al 2014). The main strategy for protection from storm surge is moving out of harm 's way ahead of the storm.…”
Section: Bac Kg R O U N Dmentioning
confidence: 99%
“…They typically turn first to their local television station for information and then seek confirmation from other sources such as national television stations, cable weather stations, websites, and social networks (Dash and Gladwin 2007;Zhang et al 2007;Lazo et al 2009;Taylor et al 2009;Morss and Hayden 2010;Sherman-Morris et al 2014). The main strategy for protection from storm surge is moving out of harm 's way ahead of the storm.…”
Section: Bac Kg R O U N Dmentioning
confidence: 99%
“…Our analysis indicated that the partnerships within the hurricane warning system are generally successful, in that each group plays a unique and critical role and that, together, the groups make information about hurricane threats widely available (Taylor et al 2009;Morss and Hayden 2010). As one NHC forecaster noted, "It's amazing when you sit down and look at everything that could go wrong, and yet 99-pointsome percent of the time, the forecasts go out on time.…”
mentioning
confidence: 96%
“…Information about geographical areas at high risk from hurricanes is also improving, for example, through updated mapping, advances in storm surge modeling, and more precise determination of evacuation zones (Rappaport et al 2009; Florida Division of Emergency Management 2011). Moreover, social science research is developing a growing understanding of the factors that contribute to people's hurricane preparation and evacuation decision making (Dow and Cutter 1998;Dash and Morrow 2001;Gladwin et al 2001;Gladwin and Morrow 2005;Dash and Gladwin 2007;Zhang et al 2007;Taylor et al 2009;Lazo et al 2010;Morss and Hayden 2010). Here we complement these efforts by examining the starting point of the warning and response process-that is, how information about forecasts, warnings, and recommended protective actions is created and communicated when a hurricane threatens.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…(20)(21)(22)(23) Because residents' memories are likely to be imperfect, we currently know far less than we would like to about the dynamics of how information search patterns change over time during the course of storm threats, the kinds of information that serve to trigger decisions to take protective action, and how these dynamics vary across individuals. Perhaps most critically, we also have little basis for answering important counterfactual questions about how levels of preparedness might be different if alternative kinds of information were provided to residents.…”
Section: The Dynamics Of Hurricane Risk Responsementioning
confidence: 99%